Melatonin changes energy metabolism and reduces oncogenic signaling in ovarian cancer cells - Silveira, Henrique Spaulonci [UNESP]; Cesário, Roberta Carvalho [UNESP]; Vígaro, Renan Aparecido [UNESP]; Gaiotte, Leticia Barbosa [UNESP]; Cucielo, Maira Smaniotto [UNESP]; Guimarães, Fernando; Seiva, Fábio Rodrigues Ferreira [UNESP]; Zuccari, Debora Aparecida P.C.; Reiter, Russel J.; Chuffa, Luiz Gustavo de Almeida [UNESP] (Elsevier, 2024)
Ovarian cancer (OC) adjusts energy metabolism in favor of its progression and dissemination. Because melatonin (Mel) has antitumor actions, we investigated its impact on energy metabolism and kinase signaling in OC cells (SKOV-3 and CAISMOV-24). Cells were divided into control and Mel-treated groups, in the presence or absence of the antagonist luzindole. There was a decrease in the levels of HIF-1α, G6PDH, GAPDH, PDH, and CS after Mel treatment even in the presence of luzindole in both OC cells. Mel treatment also reduced the activity of OC-related enzymes including PFK-1, G6PDH, LDH, CS, and GS whereas PDH activity was increased. Lactate and glutamine levels dropped after Mel treatment. Mel further promoted a reduction in the concentrations of CREB, JNK, NF-kB, p-38, ERK1/2, AKT, P70S6K, and STAT in both cell lines. Mel reverses Warburg-type metabolism and possibly reduces glutaminolysis, thereby attenuating various oncogenic molecules associated with OC progression and invasion.
Keywords: Cellular metabolism; Glutaminolysis; Kinase signaling; Melatonin; Ovarian cancer; Tumor progression; Warburg effect